2021
DOI: 10.1177/02841851211063007
|View full text |Cite
|
Sign up to set email alerts
|

Multi-echo Dixon and breath-hold T2-corrected multi-echo single-voxel MRS for quantifying hepatic iron overload in rabbits

Abstract: Background Three-dimensional (3D) multi-echo-Dixon (ME-Dixon) and breath-hold T2-corrected multi-echo single-voxel MR spectroscopy (HISTO) can simultaneously quantify liver fat and liver iron. However, their diagnostic efficacy and application scope for quantitative iron in co-existing fatty liver have not been adequately evaluated. Purpose To evaluate the accuracy of ME-Dixon and HISTO for quantitative analysis of hepatic iron in rabbits with iron deposition and fatty liver using liver–iron concentration (LIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[ 17 ] Studies have shown that MR techniques for detecting iron deposits in the liver correlate well with liver biopsies. [ 10 , 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Studies have shown that MR techniques for detecting iron deposits in the liver correlate well with liver biopsies. [ 10 , 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[18] HISTO is a T2-corrected multi-echo single-voxel MR spectroscopy sequence that acquires multiple echoes in a single acquisition within one breath-hold. [10,19,27] We use this sequence to quantify liver iron deposition because of its inherent ability to separate water resonance from other confounding sources of proton resonance. Zhan et al reported that the ability of MRS to detect hepatic iron overload is equal to that of multi-echo Dixon at 3T.…”
Section: Tablementioning
confidence: 99%
“…[16][17][18] Recently, high-speed T 2 -corrected multiecho (HISTO) MRS was developed to assess lipids by using multiple short-echo times to correct T 2 bias and using long repetition times to correct T 1 bias by enabling the simultaneous acquisition of multiple echoes, 19,20 which is faster and more accurate in acquiring and measuring lipid components than traditional MRS. [21][22][23] Previous studies have shown the benefit of HISTO-MRS for the precise quantitative assessment of fatty deposition in the liver. 23,24 However, only one study has examined the utilization and feasibility of HISTO-MRS as a rapid and noninvasive MRS technique for quantifying the fat infiltration of skeleton muscles in children with confirmed DMD, 25 Meanwhile, the relationship between muscle fat infiltration measured by HISTO-MRS and clinical motor functional ability remains unknown. The predictive value of HISTO-MRS for the loss of ambulation of DMD remains lacking.…”
mentioning
confidence: 99%